Monitoring attentional processes for intelligent channelling of educational tasks - Heyer Wollenberg, Patrick (2014)
Aims: - Detection of attention: Map a lexicon of body postures to binarizedattentionallevels (Experiment I). - Attribution of attention: Identify postural features leading to appreciation of attention by third parties (e.g. educators) (Experiment II).